Face Recognition System for Fare Elections - T.Venkata Ramakoteswararao, Y.Bhaskarrao (International Journal of Advanced Science and Technology, 2020)
Right now, new validation strategy in voting system utilizing facial recognition of the voter is utilized. Presently in India, there are two kinds of casting a ballot framework by and by. They are Ballet paper and Electronic Voting Machines (EVM), yet both of the procedure has some negative marks. The voters need to go to circulated places and remain in a long line to make their choice, because of these reasons the majority of the individuals passes up on the opportunity of casting their votes. The individuals who are not qualified to cast a ballot can likewise cast their votes by undesirable methods, which may cause different issues. Here we have three degree of security in casting a ballot procedure. The main level is the check of unique id number (UID), second level is the confirmation of election id number (EID) and third level is face acknowledgment. The security level of our technique has been exceptionally improved by the utilization of new technique for every voter. The verification of the client in the technique is improved by utilizing face recognition, which will have the option to recognize whether the client is confirmed client or not.